Effects of physical activity participation on subjective well-being of Chinese residents: mediating effects of physical health status and perceived social development - Pingqiang Wei; Ting Qin; Chengyi Zhu (Frontiers in Psychology)
BackgroundPhysical exercise participation can effectively improve the subjective well-being of Chinese residents; however, further research is needed to understand how this participation influences their well-being. This study aims to explore the influence mechanism of physical exercise participation on the subjective well-being of Chinese residents and the mediating role of physical health status and social development cognition in this relationship.MethodsBased on the data from China’s comprehensive social survey in 2021, 7,923 valid samples were selected. Three variables, such as physical exercise participation, physical health status, and social development cognition, were used to explore residents’ subjective well-being. Multiple linear regression models, structural equation models, and bootstrap methods were employed to assess the mediating effects of these variables.Results(1) Physical exercise participation can improve residents’ subjective well-being (β=0.084, t = 4.67) and promote the development of positive psychology. (2) Physical health status has a mediating effect on the impact of physical exercise participation on residents’ subjective well-being, with a mediating effect calculated at 0.05 (95% CI [0.01, 0.09]). (3) The cognitive level of social development has a mediating effect on the influence of physical exercise participation on residents’ subjective well-being, with a documented mediating effect of 0.04 (95% CI [0.01, 0.08]). (4) Both physical health status and social development cognition collectively exhibit a chain mediating effect on the relationship between physical exercise and subjective well-being, with a combined mediating effect of 0.07 (95% CI [0.04, 0.10]).ConclusionParticipation in physical activity has a positive effect on residents’ subjective well-being, with physical health status and social development cognition serving as chain mediators in this relationship. Consequently, it is recommended that both government and various societal sectors intensify efforts to promote physical activity. By creating supportive environments that facilitate regular physical exercise, we can enhance the health and happiness of the population at large.